Knowledge management strategy of a law firm : Dr. Kabir and Associates. - Jalil, Md. Abdul (Universiti Malaysia Perlis, 2012)
We all know that knowledge is a crucial need in all aspects of our lives especially in effective business management. To succeed in the business it is essential to survive in competition with similar competitors in the market. To effectively complete with other competitors in the market, we need knowledge and innovation capacity. Now acquiring or capturing knowledge is not all, the most important point is that the acquired knowledge must be managed properly to ensure stable and continuous growth in the business organization. The objective of this project paper is to evaluate the effectiveness of the knowledge management strategy undertaken by a law firm named ‘Dr. Kabir and Associates’. Descriptive and analytical research methodology has been applied in this research project. Interview has also been taken from the senior lawyers of the law firm and the gist of the interview has been used in writing the project paper.